The development of a method for visualizing the states of the national security system - Kuchuk, Nina; Shyshatskyi, Andrii; Zhuravskyi, Yurii; Stasiuk, Tetiana; Nalapko, Oleksii; Sliusar, Peter; Protas, Nadiia; Shaposhnikova, Olena; Pronin, Sergii; Havryliuk, Oksana (Technology audit and production reserves, 2023)
The scientific task, which is solved in the research, is the cognitive display of the state of the national security system with a complex hierarchical structure. As a rule, images are created individually taking into account a specific application field and interpreted by an expert (a group of experts) based on accumulated knowledge. Cognitive mapping is designed to support decision making by an expert (group of experts), monitoring and managing in real time. The object of research is the system of ensuring national security. The subject of the research is the functioning of the national security system. The research developed a method of visualization of the states of the national security system. An overview of the methods of visual graphic presentation of information about the state of multidimensional objects and systems was carried out. The novelties of the proposed method are: ‒ creation of a visual, multi-level and interconnected description of the national security system; ‒ increasing the efficiency of decision making while assessing the state of the national security system; ‒ solving the problem of falling into global and local extremes while assessing the state of the national security system; ‒ combination of graphic and numerical display of controlled state parameters of the national security system; ‒ avoiding the problem of loops while visualizing the state of the national security system in real time. The specified method should be implemented in specialized software, which is used to analyze the state of the national security system and make management decisions.